Research Progress and Hot Topics in Telerehabilitation for Hip or Knee Arthroplasty - Liqiong Wang; Liming Zhang; Chengqi He (Orthopaedic Surgery)
ABSTRACT Objective Many publications on telerehabilitation for hip or knee arthroplasty have been published in recent years. However, no specific studies have attempted to characterize research hotspots, global research collaborations, or trends related to telerehabilitation after hip or knee arthroplasty. Therefore, the aim of this bibliometric analysis was to provide an overview of the current status of research and map the research landscape on telerehabilitation for joint replacement to understand current trends, identify research gaps, and guide future research directions. Methods The Web of Science Core Collection and PubMed were comprehensively searched to identify all relevant English‐language documents published from 2003 to June 7, 2024. Data from these published studies were then cleaned and structured. CiteSpace and VOSviewer were used to conduct the bibliometric visualization and comparative analysis of countries, institutions, journals, authors, references, and keywords. Then, the map illustrating the research hotspots and knowledge structure was plotted based on the analysis results. Results A total of 229 records were obtained, and the number of articles published has increased steadily over the investigated period. The largest increase was observed in 2022. With the highest number of publications and centrality, the United States was the most influential country. The University of Sherbrooke was the most productive institution. Author Boissy P. ranked first in terms of the number of publications, while Tousignant M. ranked highest in cited authors, with 7 publications and 65 citations. The Journal of Arthroplasty published the greatest number of articles, with 29 publications. The most popular keywords from 2018 to 2023 were “home telerehabilitation,” “older adults,” and “physical therapy”. In terms of the strongest citation burst, the top five keywords were associated with “total knee arthroplasty,” “in home tele rehabilitation,” “physical activity,” “motion,” and “range.” The frontier keywords were “patient satisfaction,” “mobile application,” “self‐efficacy,” “fear avoidance model,” “home assessment tool,” and “cost benefit analysis.” Conclusions The current status and trends in telerehabilitation for hip or knee arthroplasty are presented. A major concern at present is physical therapy for home telerehabilitation in the elderly. In the future, mobile app–based telerehabilitation programs for arthroplasty will continue to be encouraged, and some outcomes, such as “patient satisfaction,” “self‐efficacy,” and “cost benefit analysis,” are expected to receive more attention. Our work will serve as a valuable resource, providing fundamental references and a directional guide for future research.